Pharmacokinetic interaction between udenafil and dapoxetine: a randomized, open-labeled crossover study in healthy male volunteers - Kim YH; Choi HY; Lee SH; Jeon HS; Lim HS; Bahng MY; Bae KS (Dove Medical Press, 2015)
Yo Han Kim,1 Hee Youn Choi,1 Shi Hyang Lee,1 Hae Sun Jeon,1 Hyeong-Seok Lim,1 Mi Young Bahng,2 Kyun-Seop Bae1 1Department of Clinical Pharmacology and Therapeutics, Asan Medical Center, College of Medicine, University of Ulsan, 2Clinical Development Department, Dong-A ST Co, Ltd, Seoul, Republic of Korea Background: “Udenafil” is a phosphodiesterase-5 inhibitor indicated for erectile dysfunction. “Dapoxetine” is a serotonin transport inhibitor indicated for premature ejaculation. The aim of the study reported here was to investigate the pharmacokinetic drug interaction between udenafil and dapoxetine in healthy male subjects. Methods: An open-label, three-treatment, six-sequence, three-period crossover study was performed in healthy male subjects. In varying sequences, each subjects received single oral doses of udenafil 200 mg, dapoxetine 60 mg, and both treatments. The periods were separated by a washout period of 7 days. Serial blood samples were collected up to 48 hours after dosing. The plasma concentrations of udenafil and dapoxetine were determined using a validated liquid chromatography-tandem mass spectrometry method. Pharmacokinetic parameters were obtained by non-compartmental analysis. Tolerability was assessed throughout the study. Results: Twenty-three healthy subjects completed the study. The geometric mean ratios of the area under the plasma concentration–time curve from time 0 to last measurable time point and measured peak plasma concentration for udenafil were 0.923 (90% confidence interval [CI]: 0.863–0.987) and 0.864 (90% CI: 0.789–0.947), respectively. The geometric mean ratios of the area under the plasma concentration–time curve from time 0 to last measurable time point and measured peak plasma concentration for dapoxetine were 1.125 (90% CI: 1.044–1.213) and 0.837 (90% CI: 0.758–0.925), respectively. There were no serious adverse events reported, and none of the subjects dropped out due to adverse events. Conclusion: Udenafil was found to have no clinically significant pharmacokinetic interactions with dapoxetine. The concurrent administration of udenafil and dapoxetine was generally well tolerated. Keywords: drug interaction, pharmacokinetics, erectile dysfunction, premature ejaculation